RTI ( amendment) act, 2019: Athreat to participatory demoracy - Yadav, Tanvi. and Sole, Nagendra Ambedkar (South Asian Journal of Socio-Political Studies)
In democracy awareness of people is the only source surviving. Right to information is considered as the fundamental human right under the preview of UDHR at International level. - Reproduced
Keywords: Right to knwo, Democracy, Participation, Judiciary & RTI